Analisis Risiko Dan Peluang Bisnis Praktik Jasa Titip Online Di Media Sosial (Instagram) Dalam Perspektif Hukum Islam - Sherli Sadila; Sundari, Siti (La Zhulma | Jurnal Ekonomi dan Bisnis Islam, 2024)
The aim of this research is to determine the view of Islamic law regarding the practice of online entrustment services on social media, and what risks and opportunities are felt by online entrustment service business actors on social media. This research is included in the type of qualitative research. Data collection for this thesis is the result of observation, literature study, interviews and documentation. In data analysis techniques, this research uses several stages, namely data collection, data presentation, data reduction, and finally drawing conclusions. Based on the results of the research, it is concluded that, firstly, the practice of entrusting services on social media in the view of Islamic law is legal and permissible as long as it does not violate the rules and there are no arguments that forbid it. The contract from the practice of jastip itself is a wakalah bil ujrah contract, namely an agreement between both parties (representative and muwakkil), where a muwakkil gives authority to the representative to do something in exchange for giving ujrah (fee/wages) to the representative. Second, the risk of the practice of entrusting services, namely the potential for financial losses due to additional fees, import duties and taxes; product damage, and business competition. Meanwhile, opportunities for entrusted service practice include the use of information and communications technology (ICT); consumer expansion, and increasing relationships.